The Development Model of the Sharing Economy in the Era Of Big Data: The Development Path of Shared Bicycles - Luo, Jia (International Journal of Computer Science and Information Technology, 2024)
With the rapid development of the Internet and information industry, the sharing economy equipped with the Internet and big data systems has become a technological economic model. In the field of transportation, the shared bicycle industry has also reached a new height. Emerging industries bring fresh vitality, and the shared economic model brings momentum to market development and strongly affects the traditional economy. At the same time, the research on shared bicycles involves research from multiple angles such as economics, management science, and social governance, and has increasingly academic value. This article explores the performance of shared bicycles in the development of the sharing economy, and explains the elements, impacts, and future prospects of shared collaboration.